The skin as a window to the blood: Cutaneous manifestations of myeloid malignancies. Issue 6 (November 2017) - Li, Alvin W.; Yin, Emily S.; Stahl, Maximilian; Kim, Tae Kon; Panse, Gauri; Zeidan, Amer M.; Leventhal, Jonathan S.
Abstract: Cutaneous manifestations of myeloid malignancies are common and have a broad range of presentations. These skin findings are classified as specific, due to direct infiltration by malignant hematopoietic cells, or non-specific. Early recognition and diagnosis can have significant clinical implications, as skin manifestations may be the first indication of underlying hematologic malignancy, can reflect the immune status and stage of disease, and cutaneous reactions may occur from conventional and targeted agents used to treat myeloid disease. In addition, infections with cutaneous involvement are common in immunocompromised patients with myeloid disease. Given the varying presentations, dermatologic findings associated with myeloid malignancies can pose diagnostic challenges for hematologists and dermatologists. In this clinical review intended for the practicing hematologist/oncologist, we discuss the presentation, diagnosis, treatment, and prognostic value of the most common cutaneous manifestations associated with myeloid malignancies using illustrative macro- and microscopic figures and with a special emphasis on practical considerations.